Nano Lipid Carrier System Development for Dapagliflozin: Central Composite Design Approach (Asian Journal of Pharmaceutics (AJP), 2024)
Original Research: The content involves original experimental work on the development of a nano lipidcarrier system for Dapagliflozin using a central composite design approach. Methodology: It describes specificmethodologies, such as the central composite design (CCD), and includes experimental data and results. ObjectiveAnalysis: The aim is to optimize a drug delivery system, which typically falls under the category of researcharticles in scientific journals.